Tourism as a Survival Strategy for Kerala’s Plantation Sector: A Tantalising Agenda in the Era of Globalisation? - Tharian George. K
The establishment of WTO and its rule based globalisation agenda have heralded an increasing reliance on invisible forces of market. This process of change has the potential of generating irreversible webs of complex issues by resorting to unsustainable strategies for short-term gains. This paper raises a few questions on tourism as a survival strategy for Kerala’s ailing plantation sector from a historical perspective. An important malady affecting the plantation sector has been an insignificant share of farm gate price in the value chain as the surplus generated has been primarily appropriated by the organised trading capital segment. One of the survival Strategies evolved by the planting community has been eco-tourism in the plantations for reaping maximum returns in the short-run. However, tourism as a survival strategy for Kerala’s plantation sector has serious limitations from a long-term perspective.